Managing plant under stress: a challenge for food security - Ismail, Mohd Razi (Universiti Putra Malaysia Press, 2011)
Allah subhanahuwataala , The Almighty is the Only and Unique Owner of everything including climate. The creation of climate is unchallengeable but Allah provides us the mind to explore adaptation to what has been created. The global climate change causes various environmental stresses that led to major impact on human life. In agriculture, environmental stresses represent the most limiting factors to food productivity. Environmental stress impact not only crops which are presently being cultivated, but also are significant barriers to the introduction of crop plants into areas which are not at this time being used for agriculture. A significant problem for agriculture in the world is the major variation in crop yields from year to year due to variations in environmental stresses such as drought, flooding, salinity and high temperature. Stressful environments are often characterized by the occurrence of more than one stress simultaneously. Thus, drought is often associated with temperature, drought with salinity and flooding with ion toxicity. In urban environments, air pollutants are often associated with high temperature and low intercepted radiation with the occurrence of haze. Managing these environmental stress elements is a major consideration to achieve sustainability in agriculture system. Any contribution that relates understanding of factors and managing environmental stress will be of special interest of many years to come. Rice is fundamental for food security with approximately 3 billion people, about half of the world population, eating rice every day In coming decades, downward pressures on food stocks are expected to intensify. In addition to increased demand from the ever increasing population, the forthcoming climate change can also affect rice production. In Malaysia, national food policy under 10th Malaysia plan projected that 90% SSL (self sufficiency level) will need to be achieved by 2015 while the present SSL is 65%. To achieve the target, at least two major challenges, (i) low yield of rice, and (ii) climate change should be considered during innovative research formulation on rice. Low average yield of rice (4 t ha-1), features eight granary areas in Malaysia, can be considered a major threat for national food security The ultimate aim is to sustain yield in resources that are increasingly limited under a changing climate. This will led to ensuring food security for present and future generation to come.